Integrating Tradition into Legal Reform: Reconstructing the Role of Reconciliatory Customary Judges in Diversion Processes within the Interplay of Islamic, Customary, and National Law - Siti Zubaidah; Musakkir Musakkir; Syamsuddin Muchtar; Wiwie Heryani; Ahmad Masum (Faculty of Sharia (Islamic Law) at Fatmawati Sukarno State Islamic University Bengkulu, 2025)
Juvenile cases in conflict with the law are ideally resolved through diversion, a restorative mechanism that prioritizes recovery, avoids stigmatization, and encourages participatory dialogue among stakeholders. However, in practice, diversion implementation in Indonesia often encounters systemic and cultural barriers, especially when relying solely on formal legal institutions. This study explores the role of Reconciliatory Customary Judges (RCJs) in Tana Toraja as culturally embedded mediators and reconstructs their potential function within the national diversion framework. Using a mixed-methods approach, the research combined qualitative interviews with customary leaders (to parenge), religious figures, and law enforcement actors, alongside quantitative surveys conducted among community members. The empirical findings reveal that RCJs hold significant social legitimacy, drawn from their alignment with tongkonan kinship systems and aluk todolo norms of deliberation (musyawarah). Their mediation practices reflect Islamic principles of reconciliation (sulh) and complement the restorative justice goals of the Juvenile Criminal Justice System (UU-SPPA). The study identifies a legal pluralism in practice, wherein Islamic, customary, and national legal traditions converge. RCJs have proven effective in resolving community conflicts and are trusted across generational lines, making them ideal mediators in diversion cases. The results call for the institutionalization of RCJ roles across diversion stages, including police, prosecution, and judiciary levels, to enhance cultural responsiveness, legal legitimacy, and social restoration. This research offers a transformative framework for integrating localized wisdom into national legal reform. By recognizing RCJs as formal diversion mediators, Indonesia can bridge gaps between normative aspirations and socio-cultural realities, promoting a restorative justice system that is legally sound, culturally resonant, and constitutionally grounded